2017
DOI: 10.1177/1461444817744783
|View full text |Cite
|
Sign up to set email alerts
|

Identity and collective action via computer-mediated communication: A review and agenda for future research

Abstract: Since the start of large-scale waves of mobilisation in 2011, the importance of identity in the study of collective action via computer-mediated communication (CMC) has been a source of contention. Hence, our research sets out to systematically review and synthesise empirical findings on identity and collective action via CMC from 2012 to 2016. We found that the literature on the topic is broad and diverse, with contributions from multiple disciplines and theoretical and methodological approaches. Based on our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 87 publications
(151 reference statements)
3
46
0
Order By: Relevance
“…Political institutions and others had already classified the GIM as right wing (Bundesministerium des Innern, für Bau und Heimat, 2019); the strategic framing this study identified and the ethno-pluralistic topics can be seen as a modern version of racism: cultural racism (e.g., Bruns et al, 2015;Elgenius & Rydgren, 2019;Schmidt, 2017;Virchow, 2015). Frames such as Anti-migration and Recruiting for the GIM prove that the GIM clearly used its Facebook page to initiate offline collective action (Harlow, 2011;Priante et al, 2018;Virchow, 2015). However, there are no indicators showing how successful they have been at reaching these goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Political institutions and others had already classified the GIM as right wing (Bundesministerium des Innern, für Bau und Heimat, 2019); the strategic framing this study identified and the ethno-pluralistic topics can be seen as a modern version of racism: cultural racism (e.g., Bruns et al, 2015;Elgenius & Rydgren, 2019;Schmidt, 2017;Virchow, 2015). Frames such as Anti-migration and Recruiting for the GIM prove that the GIM clearly used its Facebook page to initiate offline collective action (Harlow, 2011;Priante et al, 2018;Virchow, 2015). However, there are no indicators showing how successful they have been at reaching these goals.…”
Section: Discussionmentioning
confidence: 99%
“…These new dynamics have been described using the concept of connective action (Bennett & Segerberg, 2012;Priante et al, 2018). Among the characteristics of connective action are the use of general instead of political content frames, hence, frames that can be personalized and adapted to various situations; the use of digital media and social networks with less formal ties, bringing distant people closer together; and self-organization without central or leading actors (see also Anduiza et al, 2014;Bennett, 2012).…”
Section: Social Movements and Online Communicationmentioning
confidence: 99%
“…While group identification was found as the strongest antecedent of collective actions in previous studies (Priante et al, 2018;van Zomeren et al, 2008), the increased use of digital platforms that gave rise questioning the mechanisms of collective actions led to a need for the current study. Besides, studies on this topic are diverse with contributions from multiple disciplines that use various theoretical and methodological approaches.…”
Section: The Current Studymentioning
confidence: 93%
“…Collective action is defined as the joint conduct of group members who aimed to improve the position of their own group or to reach a common group goal (Wright, Taylor, & Moghaddam, 1990). The well-known approaches of collective action are based on the findings that social identification is either the strongest predictor of collective action participation or play an essential role in mobilization and participation (e.g., Drury & Reicher, 2009;Jost et al, 2012;Klandermans, 1997;Priante, Ehrenhard, van den Broek, & Need, 2018;Stürmer & Simon, 2004;van Zomeren, Postmes, & Spears, 2008). For instance, The Elaborated Social Identity Model of Crowd Behavior (ESIM; Drury & Reicher, 1999, 2000Reicher, 1996) posits that collective actions are fundamentally group phenomenon and characteristically intergroup encounters because only shared self-categorization provides definitions of appropriate and possible conduct, and in turn, enable people to act collectively.…”
Section: Social Psychological Accounts Of Collective Actionmentioning
confidence: 99%
See 1 more Smart Citation